IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN BAHASA INDONESIA: TANTANGAN DAN PELUANG DI ERA DIGITAL - Anita Candra Dewi (Almeera Education, 2025)
Abstract. This study adopts a descriptive qualitative approach using a case study method. Data collection was carried out through in-depth interviews, participant observation, and document analysis to obtain a comprehensive understanding of the implementation of the Merdeka Curriculum in the Indonesian language learning process. The subjects involved in this study included Indonesian language teachers, students, and education personnel from various schools that have implemented the Merdeka Curriculum. The data analysis method in this study adopted the model developed by Miles and Huberman, which consists of three important stages: data reduction, data presentation, and drawing conclusions. To strengthen the validity of the data, the researcher applied triangulation involving various sources and methods. This study also considered various factors that influence, both supporting and inhibiting, the implementation of the Merdeka Curriculum. Based on the results of this study, it is clear that the implementation of the Merdeka Curriculum in teaching Indonesian has a beneficial effect on increasing student participation. In particular, the project-based learning method is a special attraction for students. In addition, the use of digital technology in this curriculum opens up enormous opportunities to enrich students' learning experiences. However, there are still some challenges faced, namely related to infrastructure readiness and the need for training for teachers. The results of the study revealed that schools with better infrastructure are able to implement digital-based learning methods with a higher level of effectiveness compared to schools that still face limitations in access to technology. In addition, online learning platforms have made a significant contribution to expanding access to education for students, although there are still some obstacles in assessing learning outcomes authentically.